CHARCOT NEUROARTHROPATHY - Natalia Bertollo; Marta Calvagno (Revista de la Sociedad Argentina de Diabetes, 2014)
Charcot's neuroarthropathy (NC) is a syndrome associated with diabetic polyneuropathy (PND), characterized by fragmentation and bone and joint destruction that can lead to severe deformities and even amputation. It is a relatively painful, progressive, degenerative arthropathy of one or multiple joints, caused by an underlying neurological deficit. In 1868 Jean-Martín Charcot described, for the first time, this disease in patients with tabes dorsalis as “ataxic arthropathy.” The first case reported in the literature of neuroarthropathy in a patient with diabetes dates from 1936. Diabetes it is currently the most frequent cause of neuroarthropathy. The objective of this review is to provide an overview of Charcot's neuroarthropathy in terms of pathogenesis, classification, clinical presentation, diagnosis and treatment, with special emphasis on new concepts in pathogenesis and treatment.